Multiplexed Intact-Tissue Transcriptional Analysis at Cellular Resolution - Sylwestrak, Emily Lauren; Rajasethupathy, Priyamvada; Wright, Matthew Arnot; Jaffe, Anna; Deisseroth, Karl (Cell, 2016)
In recently developed approaches for high-resolution imaging within intact tissue, molecular characterization over large volumes has been largely restricted to labeling of proteins. But volumetric nucleic acid labeling may represent a far greater scientific and clinical opportunity, enabling detection of not only diverse coding RNA variants but also non-coding RNAs. Moreover, scaling immunohistochemical detection to large tissue volumes has limitations due to high cost, limited renewability/availability, and restricted multiplexing capability of antibody labels. With the goal of versatile, high-content, and scalable molecular phenotyping of intact tissues, we developed a method using carbodiimide-based chemistry to stably retain RNAs in clarified tissue, coupled with amplification tools for multiplexed detection. The resulting technology enables robust measurement of activity-dependent transcriptional signatures, cell-identity markers, and diverse non-coding RNAs in rodent and human tissue volumes. The growing set of validated probes is deposited in an online resource for nucleating related developments from across the scientific community.